An Update on Breast Cancer Multigene Prognostic Tests—Emergent Clinical Biomarkers - Vieira, André Filipe; Schmitt, Fernando (Frontiers in Medicine, 2018)
Multigene signatures generate crucial prognostic information particularly useful for cancer patients where clinical parameters and traditional immunohistochemical markers alone lead to equivocal prognosis. Clinicians are now provided with molecular tools that assist in the outline of adjuvant therapies, namely helping decide on the extension of adjuvant endocrine therapy or on suppressing adjuvant chemotherapy in patients were toxic effects are particularly deleterious or when this treatment is fundamentally not needed. The importance of cancer multigene prognostic signatures is well elucidated in the guidelines for adjuvant systemic therapy in early-stage breast cancer and the guidelines on disease staging that are progressively integrating gene expression assays as classification biomarkers. In addition to the predictive and prognostic value, some genetic tests provide intrinsic subtyping classification. Herewith, we compare the molecular tests OncotypeDX, MammaPrint, Prosigna, EndoPredict, Breast Cancer Index, Mammostrat and IHC4 and report the eligibility of each one in the suitable setting. Through to now, there is not a commercially available multigene test that makes recommendations regarding adjuvant treatment for HER-2 and triple negative breast cancers. Thus, these patients still receive adjuvant chemotherapy. Importantly, triple negative carcinomas are very heterogeneous regarding prognosis and new molecular signatures that decipher this very heterogeneous subgroup of breast cancer may improve the clinical management of the disease.